Measurement and evaluation of anisotropic thermophysical parameters of lithium-ion battery electrode stack: An experimental and numerical study - Muhammad Wasim Tahir; Muhammad Yousaf Arshad; Huma Hussain; Nam Nghiep Tran; Anam Suhail Ahmad (Next Energy)
The development of advanced electrode materials and their complex formulations has made it increasingly difficult to obtain accurate thermophysical parameters of the active zone in lithium-ion cells. These parameters, such as thermal conductivity and specific heat capacity, are crucial for optimizing the performance and safety of the battery. Conventional methods for obtaining these measurements often require expensive and sophisticated laboratory equipment, which limits accessibility and ease of use. An innovative hybrid approach is presented for measuring the thermophysical parameters of the active zone in lithium-ion batteries. This method combines experimental measurements with numerical simulations to determine anisotropic thermal conductivity, specific heat capacity, and the density of the electrode stack. A key aspect of this approach is the use of low-viscosity liquid paraffin to simulate the effects of the electrolyte. The through-plane and in-plane thermal conductivities of both wetted and dry specimens are measured, while the specific heat capacity is approximated numerically. This simple, cost-effective technique eliminates the need for specialized and expensive lab equipment. The through-plane thermal conductivity of the wetted specimen was found to be 2 orders of magnitude greater than that of the dry specimen, while the difference between the in-plane thermal conductivities of the wetted and dry specimens was negligible. The errors in the measured values of through-plane and in-plane thermal conductivities were approximately 4% and 2%, respectively, while the numerically approximated specific heat capacity showed an error of around 2.5%. All measured parameters were found to be within reported ranges. A 3D lumped thermal model incorporating the measured thermophysical parameters was simulated using the commercial software ANSYS Fluent to examine the effects of thermal anisotropy. The simulation results were validated against experimental data and were found to be in good agreement.